Pengaruh Mental Practice Terhadap Penampilan Atlet Pemula Pencak Silat Kategori Seni Tunggal Baku Jurus Tangan Kosong (di SDN Kejawen Putih II Surabaya) - Mungit Soedianto, (Pendidikan Sekolah Dasar, 2010)
Johansyah lubis declare a single category is a category of the championship which featured a martial arts fighter demonstrate expertise in a single raw stance is correct, accurate, and steady, full of inspiration with his bare hands and weapons. Program is a unity of mental practice program overall. So who should regulate trainer schedules. A good martial arts training should be focused on physical aspects, techniques, strategies and mentality of a champion. So with the existence of mental practice will help athletes to improve performance. Mental visualization is a technique that we can use to construct our performance internally, as we want or expect, either in practice or in the description above championship. Based on the title of this paper is